Paremias of the Latvians and the Russians in Latgale: From the Holy Scripture to Modern Existence - Korolova, Jelena; Kovzele, Oksana; Kacane, Ilze (Respectus Philologicus, 2020)
The paper presents a comparative analysis of some selected Latvian and Russian paremias, the bulk of which has been collected in the time period since the 1970s till nowadays in the south-eastern part of Latvia – Latgale, and studied in the context of Latvian proverbs included in folklore collections and phraseological dictionaries, as well as the archival materials of the Latvian Academy of Sciences and works by Latvian folklorists. The aim of the study is to analyse prototypical paremias from the Holy Scripture and trace the history of their existence and further development among the Latvians and the Russians in the Latgale region based on the qualitative data analysis. The conducted research allows concluding that similar worldview patterns of the Latvians and the Russians are to be searched for in Christianity. The analysed proverbs testify to the fact that culture is a unifying factor for different ethnic groups living in the same region.
Keywords: proverbs; borrowings; genetic; typological parallels; variants